Management and Facilities for Organizing Worship Guidance at the Madrasa Mosque in West Java - Sugandi Miharja; Arif Rahman; Abdul Mujib (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2018)
The mosque in Madrasah has an advaced goal regarding the demands of understanding, belief and practice of religion. The mosque as an organized institution is in principle the same, which requires the availability of facilities in accordance with the number of worshipers in the madrasa. On this basis this research focuses on: (1) aspects of mosque management at the planning, implementation, control and development stages; (2) An overview of available mosque facilities; (3 Organizing human resources from various elements of the congregation. This study uses a descriptive qualitative approach. The place of research is a mosque in the madrasa environment in West Java Province. The object of research is the mosque's human resources in religious guidance activities. Data collection techniques are observation, interviews and documentation Source of water for thaharah, number of water faucets, wc rooms, prayer rooms, loudspeakers, lighting, floor pads, places to store footwear, insulating pilgrims' rooms, and pulpit requires analysis, whether the facilities are in accordance with the number of worshipers in the madrasa The involvement of pilgrims who are in the madrasa, both students, teachers and employees in giving worship especially congregational prayer is a demand.